GABBR1 has a HERV-W LTR in its regulatory region--a possible implication for schizophrenia - Hegyi, Hedi (Biology direct, 2013)
Schizophrenia is a complex disease with uncertain aetiology. We suggest GABBR1, GABA receptor B1 implicated in schizophrenia based on a HERV-W LTR in the regulatory region of GABBR1. Our hypothesis is supported by: (i) GABBR1 is in the 6p22 genomic region most often implicated in schizophrenia; (ii) microarray studies found that only presynaptic pathway-related genes, including GABA receptors, have altered expression in schizophrenic patients and (iii) it explains how HERV-W elements, expressed in schizophrenia, play a role in the disease: by altering the expression of GABBR1 via a long terminal repeat that is also a regulatory element to GABBR1.
Keywords: genové produkty env; čipová analýza proteinů; Endogenous Retroviruses; koncové repetice; Protein Array Analysis; těhotenské proteiny; Pregnancy Proteins; lidé; Terminal Repeat Sequences; endogenní retroviry; Receptors, GABA-B; Gene Products, env; receptory GABA-B; Schizophrenia; schizofrenie; Humans